In vitro degradability of corn silage and Leymus chinensis silage and evaluation of their mixed ratios on performance, digestion and serum parameters in beef cattle. Issue 6 (11th June 2020) - Zhang, Xianglun; Wang, Hongliang; You, Wei; Zhao, Hongbo; Wei, Chen; Jin, Qing; Liu, Xiaomu; Liu, Guifen; Tan, Xiuwen; Wang, Xingling; Wan, Fachun; Sun, Xiaoyu
Abstract: This study investigated the degradability of corn silage (CS) and Leymus chinensis silage (LS) in vitro, and evaluated the effect of various ratios on growth performance, digestion and serum parameters in beef cattle. A 72‐hr bath culture trial was performed to evaluate degradability and rumen fermentation characteristics of CS, LS and their combinations [67:33, 33:67, dry matter (DM) basis]. Forty Simmental steers, averaging 441.46 ± 4.45 kg of body weight (BW), were randomly allocated into four dietary treatments for 120‐d period. Diets were given as total mixed rations with a forage‐to‐concentrate ratio of 60:40 and CS:LS ratios of 100:0, 67:33, 33:67 and 0:100 (DM basis). The in vitro trial showed that DM and neutral detergent fibre (NDF) degradability decreased linearly as LS proportion increased, whereas CP degradability increased linearly. Additionally, increased acid detergent fibre (ADF) degradability was detected at 48 hr of incubation. Increasing the proportion of LS increased rumen liquor pH and decreased volatile fatty acid linearly including acetate, propionate and butyrate, whereas the ammonia‐N increased linearly at 12 and 72 hr of incubation. With increasing LS ratio, final BW, average daily gain and feed conversion ratio of steers decreased linearly, whereas DMI was not affected. Additionally, apparent digestibility of DM, organic matter, NDF and ADF linearly and quadratically decreased while ether extract apparent digestibility decreased linearly, and CP apparent digestibility was not affected. Serum glucose and urea nitrogen linearly and quadratically decreased while glutamic‐pyruvic transaminase activity linearly decreased as the proportion of LS increased. Other serum parameters including total triglycerides, total cholesterol, total protein, albumin and glutamic‐oxalacetic transaminease were not affected. Overall, enhancing ratio of LS caused inferior DM and NDF degradability but improved CP degradability in the combinations of LS and CS. A CS:LS ratio of 67:33 resulted in the best growth performance and nutrient utilization in steers.